ChemInform Abstract: Manganese‐Mediated Intermolecular Arylation of H‐Phosphinates and Related Compounds. Issue 10 (March 2015) - Berger, Olivier; Montchamp, Jean‐Luc
Abstract A convenient method using a novel Mn(II)/Mn(IV)‐catalyst system is developed for the radical functionalization of arenes with H‐phosphinate esters, diphenylphosphine oxide and H‐phosphonate diesters.